Social Value in Panggih or Temu Manten Tradition in Temanggung Wedding - Tesa Permadani (Pusat Studi Penelitian dan Evaluasi Pembelajaran, 2023)
The tradition of panggih or temu manten is an integral part of Javanese culture and becomes one of the important ceremonies in weddings in Temanggung Region. This tradition is not only a series of practical actions before the wedding, but also carries deep social values that strengthen relationships between individuals, families, and communities. This study aims to explore and analyze the social values contained in the panggih or temu manten tradition and how these values are reflected in related practices and beliefs. The research method adopted a qualitative approach with a focus on ethnography and in-depth interviews. Data were collected through direct observation during the preparation and implementation of the panggih or temu manten tradition, as well as through in-depth interviews with participants, families, traditional leaders, and local community leaders. Data were analyzed qualitatively by identifying thematic patterns that emerged from the observational and interview data. The results showed that the tradition of panggih or temu manten in Temanggung area contains social values that can be found, among others: 1) The value of mutual cooperation, 2) The value of solidarity and harmony, 3) The value of kinship and kinship, 4) The value of respect for local traditions and culture, 5) The value of moral values education, 6) The value of community roles and involvement. This research also provides deep insight into the importance of the panggih or temu manten tradition as an organizer of strong social values in Temanggung society. The social, cultural and religious implications of this tradition are also discussed as a contribution towards a better understanding of the dynamics of Javanese society.